M1 Macrophage-derived TNF-α Promotes Pancreatic Cancer Ferroptosis Via p38 MAPK-ACSL4 Pathway - Zhang, Ji-cheng; Yin, Han-lin; Chen, Qiang-da; Zhao, Guo-chao; Pu, Ning; Lou, Wen-hui; Wu, Wen-chuan (Current Molecular Medicine, 2025)
<span class=
Keywords: MAPK pathway